ANALYSIS TINGKAT KESEGARAN JASMANI ANGGOTA UKM BOLABASKET UNIVERSITAS TEKNOKRAT INDONESIA - Adityo Pratama; Rizki Yuliandra (Universitas Teknokrat Indonesia, 2020)
Physical fitness is one of the important components in doing any activities. The sport activity is closely related to the achievements that cannot be separated from several factors and one of them is physical fitness. Related to this issue, the physical fitness of basketball club members in Universitas Teknorat Indonesia has not been known yet. Therefore, this study aims to measure the physical fitness level of basketball club members in Universitas Teknorat Indonesia. This study is a qualitative descriptive study by surveying basketball members. The subject of this study is 30 members of basketball club in Universitas Teknorat Indonesia. The data collecting technique used in this study is TKJI instrument consisting of 5 item tests, they are 50-meter run test, pull up, sit up, vertical jump, and run 1,2 KM. Descriptive statistical analysis with percentages is employed in this research as the data analysis technique. The result of this study shows that the physical fitness levels of basketball club members in Universitas Teknorat Indonesia are 26,66% for 8 members, 53,3% of medium classification for 16 members, 20,1% of less classification for 6 members, and none of the members has an excellent and poor classification. Thus, the result of the physical fitness level test for members of basketball club in Universitas Teknorat Indonesia can be categorized at a medium level.Keywords: Physical Fitness, Test, Run, Push Up, Sit Up, Vertical Jump